Answer:
the answer of that is 16 x 5
Step-by-step explanation:
20 hope this helped <333333333333333333333
1.61 is the correct answer
Answer:
234
Step-by-step explanation:
We want to find the summation from n = 2 to n = 10 of the equation -4 + 5n.
We can use the summation formula:
, where a1 is the first term,
is the last term, and n is the number of terms
Here, we can say the first term occurs when n = 2:
-4 + 5n
-4 + 5 * 2 = -4 + 10 = 6
The last term will be when n = 10:
-4 + 5n
-4 + 5 * 10 = -4 + 50 = 46
The number of terms is just 10 - 2 + 1 = 9 terms.
Substitute these in:
![S=\frac{(a_1+a_n)*n}{2}](https://tex.z-dn.net/?f=S%3D%5Cfrac%7B%28a_1%2Ba_n%29%2An%7D%7B2%7D)
![S=\frac{(6+46)*9}{2}=\frac{468}{2} =234](https://tex.z-dn.net/?f=S%3D%5Cfrac%7B%286%2B46%29%2A9%7D%7B2%7D%3D%5Cfrac%7B468%7D%7B2%7D%20%3D234)
Thus, the answer is 234.
Answer:
y = - x² - 4x - 9
Step-by-step explanation:
Given
y = - (x + 2)² - 5 ← expand (x + 2)² using FOIL
= - (x² + 4x + 4) - 5 ← distribute parenthesis by - 1
= - x² - 4x - 4 - 5 ← collect like terms
= - x² - 4x - 9 ← in standard form